Lower neutrophil‐to‐lymphocyte ratio and positive programmed cell death ligand‐1 expression are favorable prognostic markers in patients treated with pembrolizumab for urothelial carcinoma. (14th June 2022) - Miyama, Yu; Kaneko, Go; Nishimoto, Koshiro; Yasuda, Masanori
Abstract: Background: Immune checkpoint inhibitors (ICIs) are effective in some cancer patients; however, they may show no efficacy in others. Predictive biomarkers are crucial for appropriately selecting the patients who receive ICI therapy. This study aimed to clarify the predictors of disease progression in urothelial carcinoma (UC) patients treated with an ICI, pembrolizumab. Methods: We analyzed the response patterns of 50 UC patients who were treated with pembrolizumab, as well as the association between survival and clinicopathological factors. Clinical factors included age, sex, body mass index, clinical courses, laboratory data, metastases, and adverse events. Pathological factors included special variant, squamous differentiation, programmed cell death ligand‐1 (PD‐L1) expression, CD8‐positive lymphocytes density, and CDKN2A/p16 homozygous deletion. Results: During pembrolizumab treatment, four (8%), 11 (22%), and eight (16%) patients achieved the best‐case scenarios of complete response, partial response, and stable disease, respectively. Twenty‐seven patients (54%) showed progressive disease. In this study, younger age, lower preoperative neutrophil‐to‐lymphocyte ratio (NLR), and positive PD‐L1 expression were significantly correlated with longer progression‐free survival and overall survival. Moreover, lower NLR and positive PD‐L1 expression were independently associated with longer OS in multivariate analysis. Conclusions: Based on our observations, lower NLR and positive PD‐L1 expression may be independent favorable prognostic markers in UC patients treated with pembrolizumab. These results suggest that both host and tumor status can reflect the effectiveness of pembrolizumab among patients with UC. Abstract : Tumor status of positive PD‐L1 expression, and host immune status of low neutrophil‐to‐lymphocyte ratio, are both prognostic markers for urothelial carcinoma patients treated with pembrolizumab.